Effects of Lime and Compost on Chemical Characteristics and Soil Hydraulic Conductivity of Alfisols at ATP Jatikerto Coffee Plantation - Lailatul Fitria; Soemarno Soemarno (Universitas Sebelas Maret, 2022)
Coffee in Indonesia is currently one of the most important plantation commodities. Inappropriate management of coffee plantations causes low soil quality especially in smallholder coffee plantations, one of which is the density (compaction) of soil in coffee plantations that has a clayey texture. This study was aimed to analyze the effect of lime and compost application on the chemical characteristics and saturated hydraulic conductivity (SHC) of the soil. The experiment was carried out at Glasshouse Agro Techno Park (ATP) Jatikerto from September 2020-February 2021. Soil samples were taken from coffee gardens at a depth of 0-30 cm and 30-60 cm. The incubation study in the greenhouse used Factorial Complete Randomized Design with 12 treatments and 3 replications. Incubation was carried out for 8 weeks. Treatment factors include the depth of the soil sample (0-30 cm and 30-60 cm); compost (0 tons ha-1, 10 tons ha-1 and20 tons ha-1) and lime (0 tons ha-1 and 2.5 tons ha-1). Results showed that the treatment combination of 2.5 ton ha-1 of lime and 20 ton ha-1 of compost gave the best results measured by the availability of N and K nutrients and an increase in the SHC. However, results in this treatment were almost the same as treatment of 2.5 ton ha-1 of lime and 10 ton ha-1 of compost. The combination of compost and lime has a significant effect on improving the chemical characteristics of the soil and the SHC of the topsoil (0-30 cm) and the subsoil (30-60 cm).